ENTEROCUTANEOUS FISTULA AFTER EMERGENCY GENERAL SURGERY: MORTALITY, READMISSION, AND FINANCIAL BURDEN - Hatchimonji, Justin S (J Trauma Acute Care Surg, 2020)
BACKGROUND: The burden of enterocutaneous fistula (ECF) after emergency general surgery (EGS) has not been rigorously characterized. We hypothesized that ECF would be associated with higher rates of post-discharge mortality and readmissions. METHODS: Using the 2016 National Readmission Database, we conducted a retrospective study of adults presenting for gastrointestinal (GI) surgery. Cases were defined as emergent if they were non-elective admissions with an operation occurring on hospital day 0 or 1. We used ICD-10 code K63.2 (fistula of intestine) to identify postoperative fistula. We measured mortality rates and 30- and 90- day readmission rates censuring discharges occurring in December or from October-December, respectively. RESULTS: 135,595 patients underwent emergency surgery; 1,470 (1.1%) developed ECF. Mortality was higher in EGS patients with ECF than in those without (10.1% vs. 5.4%; OR 1.99, 95% CI 1.67–2.36) among patients who survived the index admission. Readmission rates were higher for EGS patients with ECF than without at 30 days (31.0% vs. 12.6%; OR 3.12, 95% CI 2.76–3.54) and at 90 days (51.1% vs. 20.1%; OR 4.15, 95% CI 3.67–4.70). Similar increases were shown in elective GI surgery. CONCLUSIONS: ECF after gastrointestinal EGS is associated with significantly increased odds of mortality and readmission, with rates continuing to climb out to at least 90 days. Processes of care designed to mitigate risk in this high-risk cohort should be developed. LEVEL OF EVIDENCE/STUDY TYPE: Level II, prognostic